Synthesis and Characterization of Some Heterocyclic Compounds (Oxazepine, Tetrazole) Derived from Schiff Bases - Al-Juburi, Ruaa M (Al-Nahrain Journal of Science, 2018)
This work included synthesis of several new Schiff bases by condensation of benzidine and some aldehydes (2-hydroxy benzaldehyde, 4-N, N-dimethyl amino benzaldehyde, Pyridine-3-carboxyaldehyde) to obtain Schiff bases (1-3) and with ketones (4-hydroxy acetophenone, acetophenone, Isatin) to obtain Schiff bases (4-6). Also, new six oxazepines compounds (7-12 compounds) were synthesized through the reaction of phthalic anhydride with the prepared Schiff bases to obtain seven hetrocyclic compounds. Besides, we prepared new tetrazole derivatives from the reaction of the prepared Schiff bases with sodium azide in THF. The prepared compounds were characterized by (FT-IR, and some of them by 1HNMR, 13CNMR spectroscopy), physical properties were recorded and the biological activity was evaluated against two kinds of bacteria gram positive and gram negative.